2020
DOI: 10.1186/s12951-020-00687-2
|View full text |Cite
|
Sign up to set email alerts
|

Topically applicated curcumin/gelatin-blended nanofibrous mat inhibits pancreatic adenocarcinoma by increasing ROS production and endoplasmic reticulum stress mediated apoptosis

Abstract: Background Pancreatic adenocarcinoma (PDAC) is one of the most fatal malignancies. Surgical resection supplemented by chemotherapy remains the major therapeutic regimen, but with unavoidable resistance and systemic toxic reaction. Curcumin is a known safe natural compound that can effectively eliminate pancreatic adenocarcinoma cells in vitro, making it a promising candidate for substitution in subsequent chemotherapy. However, due to its extremely low bioavailability caused by its insolubility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…Among them, paclitaxel, curcumin and alizarin showed better inhibitory effects than the others. There have already been many studies about paclitaxel and curcumin in the pancreatic cancer field, and these agents have shown potent tumor-inhibitory capability 13 , 14 , consistent with our work. However, to date, no study has uncovered a suppressive effect of alizarin on pancreatic cancer cells.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Among them, paclitaxel, curcumin and alizarin showed better inhibitory effects than the others. There have already been many studies about paclitaxel and curcumin in the pancreatic cancer field, and these agents have shown potent tumor-inhibitory capability 13 , 14 , consistent with our work. However, to date, no study has uncovered a suppressive effect of alizarin on pancreatic cancer cells.…”
Section: Resultssupporting
confidence: 90%
“…1 ). However, there have already been many studies on paclitaxel and curcumin 13 , 14 , which have reported that these agents have potent inhibitory effects on pancreatic tumor cells, and our results are consistent with these existing studies. Nevertheless, there has not been any proof of the antitumor activity of alizarin in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 92%
“…A high level of ROS can also increase the susceptibility of tumor cells to oxidative stress-induced cell death, which could be a potential strategy for cancer therapy [44]. ROS has been found to induce endoplasmic reticulum stress and promote apoptosis of PC cells [45]. Previous studies have demonstrated that oxaliplatin induces intracellular ROS production and accumulation, which contributes to its anti-cancer activity [28].…”
Section: Discussionmentioning
confidence: 99%
“… Xu et al (2018 ) showed that a combination of curcumin and vagus nerve stimulation restored behavioral deficits by inhibiting apoptosis after cerebral ischemia, with the involvement of the Akt/ERK2 pathway. Notably, curcumin inhibits cellular damage and apoptosis by diminishing the endoplasmic reticulum stress (ERS) ( Cheng et al, 2020 ; Keshk et al, 2020 ; Zhou et al, 2022 ). Chhunchha et al (2013 ) reported that curcumin abated hypoxia-induced ERS-mediated cell death in mouse hippocampal cells by enhancing peroxiredoxin 6 (Prdx6) expressions and inhibiting NF-κB activation.…”
Section: Introductionmentioning
confidence: 99%